2019
DOI: 10.1016/j.bbadis.2018.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of soluble adenylyl cyclase against reperfusion-induced injury of cardiac cells

Abstract: sAC plays an essential role in supporting cardiomyocytes viability during reperfusion. Elevation of mitochondrial cAMP pool either by sAC overexpression or by PDE2 inhibition beneficially affects cardiomyocyte survival during reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…To prove whether the beneficial effect of PDE2 inhibition may be translated to cardiac pathology, adult rat cardiomyocytes were challenged metabolically with cyanide followed by a recovery phase. Inhibition of PDE2A with BAY60-7550 significantly improved cell viability [ 122 ]. In alignment with these results, a recent report suggested that PDE2 inhibition has a protective effect in a brain ischemia/reperfusion model, although it was delayed rather than acute effects of reperfusion that were analyzed [ 123 ].…”
Section: Functional Role Of Sac In Different Cellular Compartmentsmentioning
confidence: 99%
“…To prove whether the beneficial effect of PDE2 inhibition may be translated to cardiac pathology, adult rat cardiomyocytes were challenged metabolically with cyanide followed by a recovery phase. Inhibition of PDE2A with BAY60-7550 significantly improved cell viability [ 122 ]. In alignment with these results, a recent report suggested that PDE2 inhibition has a protective effect in a brain ischemia/reperfusion model, although it was delayed rather than acute effects of reperfusion that were analyzed [ 123 ].…”
Section: Functional Role Of Sac In Different Cellular Compartmentsmentioning
confidence: 99%
“…The group initially demonst rated that diminished mitochondrial cAMP content is detrimental and exacerbates reperfusion damage post ischemia. On the other hand, overexpression of sAC improves cardiac cell viability [160]. Elevated mitochondrial cAMP content subsequently promotes PKA-dependent phosphorylation and activation of cytochrome c oxidase, enhancing ATP synthesis and attenuates ROS production as reported elsewhere [160,161].…”
Section: Myocardial Infarction (Mi) / Reperfusion Injurymentioning
confidence: 81%
“…On the other hand, overexpression of sAC improves cardiac cell viability [160]. Elevated mitochondrial cAMP content subsequently promotes PKA-dependent phosphorylation and activation of cytochrome c oxidase, enhancing ATP synthesis and attenuates ROS production as reported elsewhere [160,161]. PDE2 inhibition during reperfusion and ischemia resulted in a specific increase in mitochondrial cAMP content, improved cell survival and accelerated recovery of cytosolic Ca 2+ homeostasis [160].…”
Section: Myocardial Infarction (Mi) / Reperfusion Injurymentioning
confidence: 84%
“…The group initially demonstrated that diminished mitochondrial cAMP content is detrimental and exacerbates reperfusion damage post ischemia. On the other hand, overexpression of sAC improves cardiac cell viability [ 184 ]. Elevated mitochondrial cAMP content subsequently promotes PKA-dependent phosphorylation and activation of cytochrome c oxidase, enhancing ATP synthesis and attenuates ROS production as reported previously [ 184 , 185 ].…”
Section: Role Of Pde2 In Cardiovascular Diseasementioning
confidence: 99%
“…On the other hand, overexpression of sAC improves cardiac cell viability [ 184 ]. Elevated mitochondrial cAMP content subsequently promotes PKA-dependent phosphorylation and activation of cytochrome c oxidase, enhancing ATP synthesis and attenuates ROS production as reported previously [ 184 , 185 ]. PDE2 inhibition during reperfusion and ischemia resulted in a specific increase in mitochondrial cAMP content, improved cell survival and accelerated recovery of cytosolic Ca 2+ homeostasis [ 184 ].…”
Section: Role Of Pde2 In Cardiovascular Diseasementioning
confidence: 99%